Karakter Tepung Komposit Talas Beneng dan Daun Kelor pada Kukis - Eko Yuniarsih; Dede Robiatul Adawiyah; Elvira Syamsir (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
Beneng taro (Xanthosoma undipes) has the highest fiber content among other taro, but its protein content is low. Processing of taro flour is still a cake product that does not last long. Cookies from beneng taro are expected to increase the added value. Moringa leaf flour is added to supplement the nutritional content of the cookies. The physical characteristics of composite flour taro beneng with Moringa oleifera leaves and the effect of adding moringa leaf flour to the physico-chemical characteristics of beneng taro cookies has been conducted. The ratio of beneng taro flour:moringa leaf flour in composite flour is 100:0; 99:1; 98:2; 97:3; 96:4; and 95:5. Water content of composite flour decreased with the addition of moringa leaf flour. The composite flour color L and a* decreased, while the colors b*, C, and 0h increased with increasing moringa leaves. The peak viscosity of composite flour paste tends to increase with the addition of moringa leaf flour up to 2%, whereas the addition of 3-5% decreases it. The viscosity breakdown, final viscosity, time reached the highest viscosity, and the temperature of the composite flour gelatinization had no effect with the addition of moringa leaf flour up to 5%. The degree of development and texture of the cookies did not affect the addition of moringa leaf flour to composite flour. The colors of L* and a* are smaller with increasing amounts of moringa leaf flour, which tends to be dark and brownish in color. The color of b*, C, and 0h of the cookies increased with the increasing number of moringa leaf flour. Cookie with 3% moringa leaf flour is most preferred and has a moisture content of 4.36%, 2.04% protein, 27.66% fat, 62.75% carbohydrate, 3.21% ash, 2.75% crude fiber, 14.9% dietary fiber, and 497.5 kcal/100 calories g.